Effect of E-Governance Training on Employee Performance at National Orientation Agency, Abuja - Anayo, Ezeh Ann; Itodo , Sylvanus Mohammed; Onuora, Chinasa Maryprudence (Kashere Journal of Politics and International Relations, 2024)
In today’s rapidly evolving digital age, e-governance has emerged as a pivotal tool for enhancing government operations and improving service delivery. The National Orientation Agency (NOA), FCT Directorate, is no exception to this paradigm shift, as it seeks to harness the potential of e-governance to augment employee performance. This study aims to examine the effect of e-governance training on employee performance in national orientation agency, FCT directorate. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to collect data. A sample of employees from various departments and levels within the NOA, FCT Directorate, participated in the study. Data analysis involves statistical techniques to determine the correlation between e-governance training and employee performance. The study adopted Vroom expectancy Theory as a framework. The study’s findings revealed that e-governance training and its alignment with job requirements and responsibilities, the impact of skills and knowledge gained from training on employee performance at the National Orientation Agency (NOA) in Abuja, among the recommendations is that the organisations should conduct a comprehensive evaluation of their e-governance training programmes to identify strengths and weaknesses. This assessment should include feedback from employees to gain insights into their specific needs and challenges